Compressive Myelopathy Caused by Arachnoid Cyst and Extramedullary Hematopoietic Tissue in a Patient with Thalassemia Major - Amaral, Leandro Custódio do; Pedrosa, Hugo Abi-Saber Rodrigues (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Thalassemias, inherited diseases of hemoglobin synthesis, are characterized by the presence of deficient hemoglobin chains that deposit in red blood cells, inducing hemolytic anemia. Extramedullary hematopoiesis represents a compensatory picture that usually affects the liver, the spleen, and lymph nodes. The involvement of the epidural space with spinal cord compression is extremely rare. Our objective was to describe the case of RMS, 31 years old, male, β-thalassemia major carrier, admitted with 2-month progressive paraparesis and urinary retention due to medullary compression by extramedullary hematopoietic tissue and thoracic arachnoid cyst, and to discuss therapeutic options. Magnetic resonance imaging (MRI) showed an extensive intraspinal and extramedullary lesion with homogeneous contrast enhancement of T3-T11 in addition to a T1-T3 cystic lesion isointense to cerebrospinal fluid (CSF). After the presumed diagnosis of spinal cord compression by proliferative hematopoietic tissue, a 10-session fractional radiotherapy treatment was immediately performed. After the radiotherapy treatment, the neurological deficits of the patient persisted despite the excellent image response with almost complete disappearance of the intraspinal mass. However, the MRI showed a persistent T1-T3 cystic lesion with significant mass effect on the spinal cord. The patient was submitted to microsurgery for total resection of this cystic lesion. In the postoperative period, the patient improved his sphincter control and motor deficits. Medullary compression by extramedullary epidural hematopoiesis is a rare complication in thalassemic patients and may be treated with surgery and/or radiotherapy. There are successful cases with the exclusive use of radiotherapy, especially in extensive lesions.
Keywords: spinal cord compression; erythropoiesis; arachnoid cysts